A New Stress Monitoring Method for Mechanical State of Buried Steel Pipelines under Geological Hazards. (24th March 2022) - Li, Xinze; Wu, Qingbai; Jin, Huijun; Kan, Wei
Abstract : Long-distance pipelines are threatened by a variety of natural geological hazards. A stress monitoring system driven by the strain-stress solution algorithm was proposed; it can achieve real-time maximum axial stress measurement by installing vibrating wire gauges (VWGs) on the surface of the pipe. To verify the effectiveness of the algorithm, a large-scale pipe mechanical loading experiment combined with a finite element model (FEM) was conducted. The results show that VWGs were reliable with a relative error of 1.19%∼7.98% compared with resistance strain gauges (SGs). The FEM was also reliable with a maximum relative error of 4.04% compared with theoretical analysis. When the reasonable combination modes of VWGs were chosen utilizing the least square method, the error of the pipe stress detection algorithm could be controlled within the range of −13.33∼16.66%. This pipeline stress monitoring technology can meet the requirement of 24-hour dynamic monitoring of the underground pipeline's mechanical state, realizing the early warning of geohazards.